2.3x*3.2=-9.4

Simple and best practice solution for 2.3x*3.2=-9.4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.3x*3.2=-9.4 equation:


Simplifying
2.3x * 3.2 = -9.4

Reorder the terms for easier multiplication:
2.3 * 3.2x = -9.4

Multiply 2.3 * 3.2
7.36x = -9.4

Solving
7.36x = -9.4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '7.36'.
x = -1.277173913

Simplifying
x = -1.277173913

See similar equations:

| -3(y-2y)+4=-3(2y-y)+8+5y | | -5+55=55 | | 50+2g=7g | | 9x^2+3x+25=11 | | (x+2)(2x-3)=x+26 | | A=M(1+rt) | | http://mathsonline.com.au/assets/interactives/images/3244-116-2.png | | factor-16x^2+34x-18= | | 0.9x-0.1(10-2x)=-0.4(x-5) | | 10-8x=10x+1 | | 8-(-3x-2)= | | 8-(-3x-1)= | | x^2-3000x+1600=0 | | -17=14x-6/-12 | | -4*(5-x)+(3-x)*(4-x)*(5-X)-4*(3-X)=0 | | 3x-6(6x-15)=-9 | | 5+x=-10+7 | | -4(5-x)+(3-x)(4-x)(5-X)-4(3-X)=0 | | -3.3x=-29.7 | | -182=6x-4(3x+29) | | ft(-4)=3x^2+7 | | 3-2(2x-4)=3x-4 | | x+.15x=1500 | | 0.6+7.9=4.6 | | f(x)=3x^2+7 | | 8x^2-53-21=0 | | 15x^2+25xy-45xz=0 | | x+x+23+23= | | 8a+5b=44 | | 4x+24=23 | | -5x+3(-6x+8)=-252 | | 10msquared= |

Equations solver categories